The Verbal Character of Advertisement Discourse and ıts of Impact Methods - Gagoshidze, Tamar (European Scientific Journal, ESJ, 2017)
Nowadays, the advertisement discourse has shown increasing appeal and is broadly analyzed by both information facilities and world-wide scientific circles. The advertisement discourse, as a linguistic research phenomena, represents complicated and intertwined sign system which aims to exert certain impact on people. It is represented as a lingual and semiotic unity aimed at the addressee the analysis of which acquired established psycholinguistic form.